Seme Stocks of Lexico-Semantic Fields – A Contrastive Study - Lelakova, Eva (Communications - Scientific letters of the University of Zilina, 2012)
The approach to the contrastive study of lexico-semantic fields and their stocks by the method of a matrix analysis is entirely new in lexical semantics. In our research paper we present the results of a comparative analysis carried out on the seme stocks of lexico-semantic fields of the nouns denoting happiness both in English and Slovak. It was preceded by dictionary analyses for the purpose to find and collect all the specified nouns. Their forms and meanings were consequently quantitatively and qualitatively analysed. The objectives of the present lexicosemantic comparison are: a character of the seme stock, individual and common meanings of English and Slovak nouns of happiness and their semantic reference to three domains of human personality.